History and Evolution of Islamic Religious Education (PAI) Policy in Indonesia - Anisya Umi Khoiroh (Penerbit Presisi Pustaka, 2026)
Islamic Religious Education (PAI) holds a strategic position in Indonesia's national education system because it plays a role in shaping character, morals, and national identity. However, Islamic Religious Education (PAI) policies are not born in a neutral space, but are constantly influenced by political dynamics, state ideology, and the relationship between the state and society. This article aims to analyze the history and evolution of Islamic Religious Education (PAI) policies in Indonesia from the colonial period to the Reformation era, and to examine the roles of the state and society in determining the direction of these policies. This research uses a qualitative approach with library research. Data were obtained from various written sources, such as laws and regulations, academic books, and relevant scientific journal articles. Data analysis was carried out through content analysis, examining PAI policies within their surrounding socio-political context. The results of the study indicate that Islamic Religious Education (PAI) policies in Indonesia have experienced fluctuating dynamics, ranging from marginalization during the colonial period, formalization and ideologization during the New Order era, to strengthening and democratization in the Reformation era. Islamic Religious Education (PAI) policies are the result of a dialectic between the state as the regulator and controller of ideology and society as the primary actors and drivers of Islamic education. Thus, the direction of Islamic Religious Education policy in Indonesia is adaptive and continues to develop in line with changing times, but still faces the challenges of globalization, radicalism, and digital technology disruption.